Analysis of Farm Household Livelihood Sustainability Based on Improved IPAT Equation: A Case Study of 24 Counties in 3 Cities in the Qin-Ba Mountain Region of Southern Shaanxi - Haiyang Shang; Yue Hu; Jiaojiao Fan; Nini Song; Fang Su (Land, 2023)
Sustainable livelihoods are those that are able to cope with and recover from stress and shocks, and that maintain or strengthen livelihood capacity and livelihood capital, without damaging the foundations of the natural environment. In this paper, the IPHACT framework was constructed by improving the classic IPAT equation, and the key factors affecting production output and livelihood sustainability, as well as the factor differences among different livelihood strategy groups, were analyzed. We took 24 counties and districts of Ankang, Shangluo and Hanzhong in the Qin-Ba Mountain area of southern Shaanxi Province as examples, using a survey of farmers’ livelihood status and livelihood capital accounting. The results show that the amplification effect of population size on the environmental impact of livelihood output is widespread and generally significant. Both livelihood sustainability and livelihood benefit passed the significance test in the multi-model analysis, and the negative effect of livelihood sustainability proved the negative correlation between the environmental impact of livelihood output and livelihood sustainability, that is, the higher the livelihood output dependent on natural capital, the greater the environmental impact. The livelihood transformation of Hanzhong City is developing in the direction of reducing the environmental impact of livelihood output, and farmers have successfully practiced green livelihood transformation by changing their livelihood strategies. On the road to common prosperity, livelihood demand will inevitably increase. Reducing the dependence on natural capital is the key to effectively enhancing the sustainability of livelihoods.